Impact of remote working on employees in IT industry - DR.GIGI G.S; MS. J SANGEETHA (The journal of contemporary issues in business and government, 2020)
Remote working and employee’s satisfaction, performance is recently being discussed often as the world is in a pandemic situation, Need for doing research has become inevitable in this field as many employees are working from home with limited resources. many significant factors are chosen for this study. The objective of this study is to know the impact of remote working in the IT industry, to find out the positive and negative consequences faced by employees while remote working, to study the influence of demographic variables on the perception of employees regarding remote working, and to give suggestions to overcome negative consequences. The questionnaire was circulated to remote workers in the IT industry. A total number of 61 respondents were contacted and were given the opportunity to participate in the survey through a convenience sampling method. The results of this research were found to be that communication is the most influencing factor of creating job satisfaction among remote employees in the IT industry and remote working is becoming the upcoming trend.